Corporate governance economic reformes and development - Reed, Darryl (ed.) (New Delhi, 2006)
This volume comprehensively discusses the history of development efforts, the corporate economy of India, and the recent changes in global political economy. In particular, it examines the changing corporate governance policies and practices in India Inc. in the face of liberalization and provides strategic recommendations for boards and managements.
Keywords: Economic reforms - India